2021
DOI: 10.1371/journal.pone.0249768
|View full text |Cite
|
Sign up to set email alerts
|

Experiences, impacts and mental health functioning during a COVID-19 outbreak and lockdown: Data from a diverse New York City sample of college students

Abstract: In March 2020, New York City (NYC) experienced an outbreak of coronavirus disease 2019 (COVID-19) which resulted in a 78-day mass confinement of all residents other than essential workers. The aims of the current study were to (1) document the breadth of COVID-19 experiences and their impacts on college students of a minority-serving academic institution in NYC; (2) explore associations between patterns of COVID-19 experiences and psychosocial functioning during the prolonged lockdown, and (3) explore sex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
54
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 39 publications
6
54
1
4
Order By: Relevance
“…Locally, activities had been business-as-usual up until one week before the March survey became available to participants. This is in stark contrast to a study of undergraduates in New York City who were surveyed around the same time but after living at least six weeks under shelter-at-home orders (López-Castro et al, 2021), of whom 17% reported the death of a family member or close friend to COVID-19. Clinically concerning symptoms of depression and anxiety were evident in 90% and 66% of students, respectively.…”
Section: Discussioncontrasting
confidence: 83%
“…Locally, activities had been business-as-usual up until one week before the March survey became available to participants. This is in stark contrast to a study of undergraduates in New York City who were surveyed around the same time but after living at least six weeks under shelter-at-home orders (López-Castro et al, 2021), of whom 17% reported the death of a family member or close friend to COVID-19. Clinically concerning symptoms of depression and anxiety were evident in 90% and 66% of students, respectively.…”
Section: Discussioncontrasting
confidence: 83%
“…This may be partly due to the effect of confounding factors on the association between the prevalence of social isolation and psychological distress during the pandemic. Several studies have reported a link between lockdown or social distancing policies and poor mental health [30][31][32][33], including a Japanese study [33]. Since lockdown or social distancing policies may also lead to an increase in the prevalence of social isolation, it is difficult to distinguish the effects of lockdown or social distancing policies from the effects of social isolation on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has exacerbated this alarming mental health trend. Eighty percent of college students report that pandemic-related closures of college campuses have negatively impacted their mental health ( Active Minds, 2020 ; López-Castro et al, 2021 ; Oh et al, 2021 ). Recent authors have identified dramatic increases in alcohol use among college students as a coping mechanism during the COVID-19 pandemic ( Bonar et al, 2021 ; Buckner et al, 2021 ; Coakley et al, 2021 ; Jackson et al, 2021 ).…”
mentioning
confidence: 99%